PESANTREN DAN MEDIASI KONFLIK KEAGAMAAN (STUDI KASUS PONDOK PESANTREN AL MUAYYAD WINDAN SURAKARTA) - Hamidah, ida; Aijuddin, Anas (Jurnal Penelitian, 2017)
AbstractSurakarta was a city which had high intensity of religious social conflict. Many conflicts potentially that was happened in Surakarta showed that there was great potential of conflict in the religiosities life. Therefore, the conflict that based on religious has to be managed as well as possible, and then transformed it to build up a peace in Surakarta. This research discussed about the roles of Pesantren of Al Muayyad Windan in which its capability to mediation the conflict in Surakarta. The questions that would be answer here were what is the rational background and how does the conflict mediation model that was done by Pesantren of Al Muayyad Windan in Surakarta. This research used the descriptive qualitative. The approach used was religious sociology approach. The technique of data collecting was done by deep interview, observation, and documentation. Furthermore, the technique of analyzing data used the interactive analysis consist of data reduction, data display, and conclusion of data. The trustworthiness in thesis was done by the data triangulation and informant review through discussion. The research finding showed that religious conflict transformation that was done by Pesantren of Al Muayyad Windan was based on the principle of the admission existence and the empowerment existence. Thus the principles were grounded on the theology percept of Aswaja that was become as the motivation to do social changes, sociological background of Surakarta that often appeared religious conflict, and community background of the Pesantren of Al Muayyad Windan that designed as the university student pesantren and pesantren of society empowerment. Conflict mediation conducted by pesantren Al Muayyad Windan Surakarta is based mediation function of an initiative for empowerment in public institutions. Functions of the institution in society was reaffirmed, pushed into the container to socialize, build silodaritas together and become a place of shared awareness.